Potential Contribution of Exosomes to the Prion-Like Propagation of Lesions in Alzheimer’s Disease - Vingtdeux, Valerie; Sergeant, Nicolas; Buee, Luc (Frontiers in Physiology, 2012)
Since the discovery of prion diseases, the concept has emerged that a protein could be a transmissible pathogen. As such, this transmissible pathogen agent can transfer its pathological mis-folded shape to the same but normally folded protein thus leading to the propagation of a disease. This idea is now extrapolated to several neurological diseases associated with protein mis-folding and aggregation, such as Alzheimer’s disease (AD). AD is a slowly developing dementing disease characterized by the coexistence of two types of lesions: the parenchymal amyloid deposits and the intraneuronal neurofibrillary tangles (NFT). Amyloid deposits are composed of amyloid-beta peptides that derive from sequential cleavages of its precursor named amyloid protein precursor. NFT are characterized by intraneuronal aggregation of abnormally modified microtubule-associated Tau proteins. A synergistic relationship between the two lesions may trigger the progression of the disease. Thus, starting in the medial temporal lobe and slowly progressing through temporal, frontal, parietal, and occipital cortex, the spreading of NFT is well correlated with clinical expression of the disease and likely follows cortico-cortical neuronal circuitry. However, little is known about the mechanism driving the spatiotemporal propagation of these lesions ultimately leading to the disease. A growing number of studies suggest that amyloid deposits and NFT are resulting from a prion-like spreading. In the present chapter, we will develop the current hypotheses regarding the molecular and cellular mechanisms driving the development and spreading of AD lesions from the window of multivesicular endosomes/bodies and exosomes.